Biomarker Phenotypes in Heart Failure with Preserved Ejection Fraction Using Hierarchical Clustering: A Pilot Study - Mitic, Valentina; Stojanovic, Dijana; Deljanin Ilic, Marina; Petrovic, Dejan; Ignjatovic, Aleksandra; Milenkovic, Jelena (Medical principles and practice, 2023)
Objectives: We hypothesized the existence of distinct phenotype-based groups within the very heterogeneous population of patients of heart failure with preserved ejection fraction (HFpEF) and using an unsupervised hierarchical clustering applied to plasma concentration of various biomarkers. We sought to characterize them as “biomarker phenotypes” and to conclude differences in their overall characteristics. Subjects and Methods: A cross-sectional study was conducted on 75 patients with HFpEF. An agglomerative hierarchical clustering was performed using the concentrations of cardiac remodeling biomarkers, BNP, and cystatin C. Results: According to the obtained heat map of this analysis, we concluded two distinctive biomarker phenotypes within the HFpEF. The “remodeled phenotype” presented with significantly higher concentrations of cardiac remodeling biomarkers and cystatin C (p < 0.001), higher prevalence of myocardial infarction (p = 0.047), STEMI (p = 0.045), atrial fibrillation (p = 0.047), and anemia: lower erythrocytes count (p = 0.037), hemoglobin concentration (p = 0.034), and hematocrit (p = 0.046), compared to “non-remodeled phenotype.” Echocardiography showed that patients within “remodeled phenotype” had significantly increased parameters of left ventricular remodeling: left ventricular mass index (p < 0.001), left ventricular mass (p = 0.001), diameters of the interventricular septum (p = 0.027), posterior wall (p = 0.003), and function alterations, intermediate pauses duration >2.0 s (p < 0.006). Conclusion: Unsupervised hierarchical clustering applied to plasma concentration of various biomarkers in patients with HFpEF enables the identification of two biomarker phenotypes, significantly different in clinical characteristics and cardiac structure and function, whereas one phenotype particularly relates to patients with reduced ejection fraction. These findings imply distinct underlying pathophysiology within a unique cohort of HFpEF.